Strategi Pemilihan Lokasi Usaha dengan Pendekatan MOORA - M Hadi Prayitno (Universitas Bandar Lampung (UBL), 2022)
One of the business strategies is to determine the location of the business, as well as a determining factor and very important in getting the best results in its business. Currently, there are many business locations that can be an alternative to running a business, such as the existence of new buildings being built, and the existence of housing that can bring business closer to the market. Taking this into account, business actors must be able to consider whether the location will be strategic or not. There are several considerations that can be taken by business owners, including building area, surrounding competitors, proximity to the market, available facilities, and rental prices. By paying attention to these things, apart from making criteria for choosing alternative business locations, it will also avoid losses for business actors by determining business locations that generate maximum profits. In this study, the author uses Multi-Objective Optimization on The Base Method of Ratio Analysis (MOORA) to determine the choice of the business location and as a strategy to develop its business. The author uses 5 criteria to choose 5 alternative business locations. Based on the calculation stages in the MOORA method, an alternative business A2, located in MGT Blok H, is generated, which is the best value from all alternative locations and is chosen as a business location that will provide business continuity, and will provide benefits in running its business.